Sustainability-driven application of waste steel and tyre rubber fibres as reinforcement in concrete: An optimization study using response surface methodology - M.A. Kareem; E.O. Ajadi; O.O. Fadipe; K. Ishola; O.A. Olawuyi; S.A. Ayanlere; O.J. Olatoyan; J.O. Adeosun; A.A. Adefajo; A.T. Oyewo; S.O.A. Olawale; W.A. Lamidi (Next Materials)
Innovative use of waste materials has proven to be effective for improving concrete’s technical properties while eliminating the threat of environmental pollution. There is paucity of research regarding the combined use of Waste Steel Fibres (WSFs) and Waste Tire Rubber Fibres (WTRFs) in concrete. Thus, this study aimed to investigate the influence of WSFs and WTRFs as reinforcement in concrete and determine their optimal fractions for enhancing the concrete strength properties using Response Surface Methodology (RSM). WSFs of 0.3-1.5% with a 0.6% increment and WTRFs of 0.3-1.5% with a 0.6% increment by concrete volume as reinforcement in concrete with water-to-cement ratio (W/C) of 0.25–0.65 with 0.2 increment were designed using the Box-Behnken Design of RSM. A total of fourteen (14) concrete mixes with a design strength of 25 N/mm2 were prepared. The fresh and hardened properties (slump, density, water absorption, 7- and 28-day compressive and split tensile strengths) of concrete were determined using standard procedures. The RSM was used to evaluate the interaction between the concrete variables and identify their optimum combination which gave the peak values of responses. Furthermore, the characteristics and sustainability of the concrete under optimum variables were compared with that of the conventional concrete. The outcomes revealed that the inclusion of WSFs and WTRFs yielded concretes with maximum slump, density, water absorption and 28-day compressive and split tensile strengths of 25 mm, 2633 kg/m3, 5%, 41 N/mm2 and 4.54 N/mm2, respectively. The optimization technique showed the optimal variables combination which yielded the peak response values of WSFs (1.40%), WTRFs (0.66%) and W/C (0.54). The nominal variance with the absolute percent error of less than (9%) between the actual experimental verified results and predicted results for all the responses validates the predictability of the model. The split tensile strength and compressive strength increased by 28.33% and 48.85%, respectively at the optimum setpoint of variable with respect to the reference concrete. In addition, the WSFs and WTRFs-reinforced concrete exhibited lower embodied CO2 emission but the embodied energy and cost are slightly higher relative to conventional concrete. Nevertheless, the embodied energy of the concrete was significantly lesser than that of concrete that used individual fibers for reinforcement. Thus, the enhancement of concrete strength properties with the prospect for sustainable fibre-reinforced concrete production through the use of waste steel and tyre rubber fibres is feasible.